Inhibition of gonadal function after chronic administration of D-Tryptophan 6, LHRH in bucks - ΚΟΥΤΣΙΛΙΕΡΗΣ Μ.; ΜΕΝΕΓΑΤΟΣ Ι.; ΞΥΛΟΥΡΗΣ Ε.; ΠΙΤΟΥΛΗΣ Σ.; ΧΑΔΙΩ Σ.; ΣΤΟΦΟΡΟΣ Ε.; ΤΟΛΗΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Plasma testosterone levels were determined in three bucks during the non-breeding season and at frequent intervals thereafter for 28 days. During this period of observation, one animal was injected daily with an LHRH superactive analoque (D TRYPTOPHAN 6, LHRH, 25pg. i.v.) whereas the other two served as controls. By the end of the 28 days period the control animals had shown a 2 fold increase in plasma testosterone whereas in the treated the plasma testosterone levels declined. The latter was associated with a decrease in the relcasable amount of LH while a prompt increase of plasma testosterone was noticed after the administration of HC G 5000 LU. Semen analysis performed 30 days after the discontinuation of the treatment with LHRH-A revealed a significant reduction in the sperm count and motility as contrasted to the control animals. These data indicate that chronic administration of LHRH-A inhibits the gonadal function of bucks and that this effected via a pituitary dependent mechanism. This findings may open new vistas in the study and control of sexual behaviour and fertility and have future applications in the programming of animal breeding.